Prognostic Impact of Memory CD8(+) T Cells on Immunotherapy in Human Cancers: A Systematic Review and Meta-Analysis - Jin, Yao; Tan, Aili; Feng, Jia; Xu, Zexi; Wang, Peiwei; Ruan, Peng; Luo, Ruijun; Weng, Yiming; Peng, Min (Frontiers in Oncology, 2021)
Objective The objective of this systematic review and meta-analysis was to determine the prognostic value of memory CD8(+) T cells in cancer patients with immunotherapy. Methods EMBASE, MEDLINE (PubMed), and Web of Science databases were searched to identify suitabile articles published before March 2021. Risk of bias on the study level was assessed using the Cochrane Bias Risk Assessment Tool. The hazard ratios (HRs) and 95% confidence intervals (CIs) of pooled progression-free survival (PFS) and overall survival (OS) were calculated using RevMan 5.4 to evaluate the prognostic impact of memory CD8(+) T cells. Results In total, nine studies were included in the final analysis. High levels of memory CD8(+) T cells were significantly closely correlated with better progression-free survival (PFS) and overall survival (OS) of cancer patients with immunotherapy (PFS, HR 0.64, 95% CI 0.53–0.78; OS, HR 0.37, 95% CI 0.21–0.65). Memory CD8(+) T cells still have significant prognostic value in cancer patients given immunotherapy alone after excluding of other interfering factors such as chemotherapy, radiotherapy, and targeted therapy (PFS, HR 0.65, 95% CI 0.48–0.89; OS, HR 0.23, 95% CI 0.13–0.42). However, high memory CD8(+) T cells levels did not correspond to a longer PFS or OS in cancer patients with non-immunotherapy (PFS, HR 1.05, 95% CI 0.63–1.73; OS, HR 1.29, 95% CI 0.48–3.48). Thus, memory CD8(+) T cells might be a promising predictor in cancer patients with immunotherapy. Conclusions The host’s overall immune status, and not only the tumor itself, should be considered to predict the efficacy of immunotherapy in cancer patients. This study is the first to show the significant prognostic value of memory CD8(+) T cells in immunotherapy of cancer patients through systematic review and meta-analysis. Thus, the detection of memory CD8(+) T cells has a considerable value in clinical practice in cancer patients with immunotherapy. Memory CD8(+) T cells may be promising immunotherapy targets.